Using mixed research approaches to understand rural depopulation - Luisa Alamá-Sabater; Vicente Budí; José María García Álvarez-Coque; Norat Roig-Tierno (Economía Agraria y Recursos Naturales)
There is a growing consensus on the need to propose specific policies to face rural depopulation. This article applies fuzzy-set Qualitative Comparative Analysis (QCA) to define the presence or absence in each municipality of the conditions leading to the presence or absence of depopulation. We also perform Exploratory Spatial Data Analysis (ESDA) of population growth to identify hotspots of rural depopulation. The methodologies prove useful to evaluate and guide regional policies that address depopulation processes in the context of a relatively urbanized region.